Combination of Psychological Intervention and Phosphodiesterase‐5 Inhibitors for Erectile Dysfunction: A Narrative Review and Meta‐Analysis. (19th March 2014) - Schmidt, Hannah M.; Munder, Thomas; Gerger, Heike; Frühauf, Sarah; Barth, Jürgen
Abstract Introduction Erectile dysfunction (ED) is an increasing health problem that demands effective treatment. There is evidence that phosphodiesterase‐5 inhibitors (PDE5‐Is) and psychological intervention (PI) are effective treatment options; however, little is known about their comparative efficacy and the efficacy of combined treatments. Aim The aim of this systematic review and meta‐analysis is to evaluate the comparative efficacy of PI, PDE5‐Is, and their combination in the treatment of ED. Main Outcome Measures Primary outcome was ED symptoms, and secondary outcome was sexual satisfaction of the patient. Methods A systematic literature search was conducted in order to identify relevant articles published between 1998 and 2012. We included randomized controlled trials and controlled trials comparing PI with PDE5‐I treatment or one of them against a combination of both. Results Eight studies with a total number of 562 patients were included in the meta‐analysis. The results of the included studies are inconclusive, though they show a trend towards a larger effect of combined treatment compared with PI or PDE5‐I treatment alone. The meta‐analysis found that, overall, combined treatment was more efficacious for ED symptoms than PDE5‐I treatment or PI alone. Combined treatment was more efficacious than PDE5‐I use alone on sexual satisfaction. No differences were found between PDE5‐Is and PI as stand‐alone treatments. None of the moderators (treatment duration, methodological quality, or researcher allegiance) altered the effects. Conclusions The combination of PI and PDE5‐Is is a promising strategy for a favorable outcome in ED and can be considered as a first‐choice option for ED patients. Stronger RCTs are required to confirm this initial finding. Schmidt HM, Munder T, Gerger H, Frühauf S, and Barth J. Combination of psychological intervention and phosphodiesterase‐5 inhibitors for erectile dysfunction: A narrative review and meta‐analysis. J Sex Med 2014;11:1376–1391.